Allonymous science: the politics of placing and shifting credit in public-private nutrition research - Penders, Bart (Life Sci Soc Policy, 2020)
Ideally, guidelines reflect an accepted position with respect to matters of concern, ranging from clinical practices to researcher behaviour. Upon close reading, authorship guidelines reserve authorship attribution to individuals fully or almost fully embedded in particular studies, including design or execution as well as significant involvement in the writing process. These requirements prescribe an organisation of scientific work in which this embedding is specifically enabled. Drawing from interviews with nutrition scientists at universities and in the food industry, we demonstrate that the organisation of research labour can deviate significantly from such prescriptions. The organisation of labour, regardless of its content, then, has consequences for who qualifies as an author. The fact that fewer food industry employees qualify is actively used by the food industry to manage the credibility and ownership of their knowledge claims as allonymous science: the attribution of science assisted by authorship guidelines blind to all but one organisational frame.